Evaluating economic stimuli in SIDS: A CGE analysis of tourism, remittances, and hotel investments in Fiji - Stephen Pratt (Annals of Tourism Research Empirical Insights, 2025)
Small Island Developing States (SIDS) face many economic challenges. Economic stimuli such as tourism expenditures, remittances, and hotel investment, can address some of these challenges. This research seeks to quantify and compare the economic effects of these three primary injections into a SIDS economy, that of Fiji. Utilizing a Computable General Equilibrium model, the study simulates the outcomes of a standardized FJ 200 million injection into each sector. The results indicate that while remittances significantly boost GDP and consumer welfare, tourism expenditures contribute positively to economic growth, particularly in the hospitality and service sectors, but have the least impact compared to the other injections. The findings suggest that policymakers should strategically enhance sectoral linkages and attract investments that foster sustainable economic growth while mitigating risks associated with increased import demand and the Dutch Disease.
Keywords: 330; CGE; Fiji; Hotel investment; Remittances; SIDS; Tourism